(untitled) (Universidad de San Andres Law Review, 2023)
This article studies the special sacrifice, one of the requisites necessary to obtain redress for the State’s lawful activity. The special sacrifice is introduced in the context of this system of State liability. The paper examines the Argentine Supreme Court’s relevant precedents in the subject. The concept of vagueness and the distinction between rules and standards are introduced in order to provide more clarity to the matter, and the conclusion is that there is still no clear case of what a special sacrifice is.